High-sensitivity micron liquid crystal sensor for detecting propyl alcohol gas and preparation method of high-sensitivity micron liquid crystal sensor
By using a highly sensitive micron liquid crystal sensor with a modified glass template instruction layer and a micro-grid structure in the sensor for detecting propanol gas, traditional sensors are easily susceptible to cross-interference, poor stability and low sensitivity in complex environments, and fast and sensitive detection of trace propanol gas is achieved, with low cost, simple operation and high efficiency.
Patent Information
- Application Number
- CN202411838334.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Traditional sensors for detecting propanol gas are susceptible to cross-interference by gases in complex environments, have poor stability, low sensitivity, and long detection cycle; at the same time, the detection equipment is complex, the accommodation requirements for the detection space are high, assembly, production and signal conversion are difficult, and the cost is high, and it cannot meet the practicality in some scenarios.
A high-sensitive micron liquid crystal sensor based on a modified glass template instruction layer is adopted. The sensor consists of a substrate, a support grid and a composite liquid crystal system. The micron grid structure carries a nematic liquid crystal composite system containing dopants to achieve a fast and sensitive optical response to trace amounts of propanol gas in the environment.
It realizes rapid and sensitive detection of trace propanol gas, with small space required for detection, simple preparation and operation, low economic cost, and stable, reversible and anti-interference. It is suitable for most scenarios for the detection of propanol gas.
Smart Images

Figure CN119804343A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a high-sensitivity micron liquid crystal sensor for detecting propanol gas, and belongs to the field of propanol detection. Background Art
[0002] Propanol is a colorless, transparent, liquid volatile organic compound (VOC) with a similar smell to ethanol. It is miscible with a variety of organic solvents such as water, alcohol, and ether. It is an important solvent in industrial synthesis, coatings, adhesives, pharmaceuticals, paints, cosmetics, food additives, and other industries. In industrial sites such as chemical production workshops and storage warehouses, a large amount of propanol vapor is easily generated. Propanol gas is flammable and forms an explosive mixture when mixed with air. It can cause safety accidents when exposed to open flames or high temperatures. In terms of physiological health, propanol has a certain degree of toxicity. Inhaling a certain amount of propanol gas can irritate the respiratory tract, causing discomfort symptoms such as headaches, dizziness, and drowsiness, and can lead to coma in severe cases. In the field of disease monitoring, propanol gas can be used as an important marker for human diseases such as lung cancer, diabetes, and intestinal dysfunction. In view of the above hazards and medical application potential of propanol gas, detecting propanol gas in the environment can reduce safety hazards in some industrial scenarios and can also be used as one of the means of medical diagnosis.
[0003] Developing new methods for detecting propanol gas can improve the efficiency of protecting against safety hazards of propanol gas in industry, and can also provide new ideas for diagnosing diseases in the medical field. Currently, commonly used methods for detecting propanol gas include gas chromatography, semiconductor detection, electrochemical detection, etc. For example, Zhang Lei et al. used the gas chromatography internal standard method to determine the propanol gas component in the mixed VOCs gas through multi-step operation, with high accuracy, good precision and strong stability; Ren Xiang et al. prepared alcohol gas sensors by hybridizing carbon materials with ferric oxide for detecting propanol gas. Although the above methods have certain responsiveness and accuracy in detecting propanol gas, they are usually expensive, difficult to make, complex signal conversion, and long analysis time, which limits their possibility of being used as portable, real-time, and rapid detection sensors. There may also be problems such as cross-interference between gases and poor reusability when they are used.
[0004] Liquid crystal material is a new functional material that has emerged in recent years. Liquid crystal is a high molecular ordered material between liquid and crystalline states. It has incomplete long-range orientation order and positional orientation order. It has both liquid-like fluidity and crystal-like anisotropy. Liquid crystal sensors use the special molecular orientation characteristics of liquid crystals to respond to specific input signals and present special optical images. Some of them can achieve optical changes observable by the naked eye. They have the advantages of portability, low cost, and simple operation. They have great application prospects in the field of propanol gas detection. Summary of the invention
[0005] Technical issues
[0006] Traditional sensors for detecting propanol gas are susceptible to cross-interference from gases in complex environments, have poor stability, low sensitivity, and long detection cycles. At the same time, the detection equipment is complex, has high requirements on the capacity of the detection space, is difficult to assemble and manufacture, and has high costs, which cannot meet the practical requirements in certain scenarios.
[0007] Technical Solution
[0008] Based on the above research status, the present invention provides a highly sensitive micron liquid crystal sensor for detecting harmful VOC gas propanol. The sensor is based on a modified glass template instruction layer as a substrate, and uses a micron grid structure to carry a nematic liquid crystal composite system containing a dopant. It can make a fast and sensitive optical response to trace propanol gas in the environment, and has stable performance, which can meet the practical requirements.
[0009] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:
[0010] An object of the present invention is to provide a highly sensitive micron liquid crystal sensor for detecting propanol gas, wherein the sensor is composed of a substrate, a supporting grid and a composite liquid crystal system; the supporting grid is placed on the substrate; and the composite liquid crystal system is filled in the supporting grid.
[0011] In one embodiment of the present invention, the substrate is a colorless transparent material that has been rinsed or soaked in a vertical modifier solution.
[0012] In one embodiment of the present invention, the vertical modifier is an organosilicon modifier, including one or more of DMOAP (dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride), DMDTAC (dimethyldodecyl[3-(trimethoxysilyl)propyl]ammonium chloride), DMHPTAC (dimethylhexadecyl[3-(trimethoxysilyl)propyl]ammonium chloride), and KH550 (γ-aminopropyltriethoxysilane);
[0013] Alternatively, it is an inorganic salt modifier, including one or more of copper perchlorate, iron perchlorate, aluminum perchlorate, and nickel perchlorate.
[0014] In one embodiment of the present invention, the solvent in the vertical modifier solution is water or alcohol.
[0015] In one embodiment of the present invention, the concentration of the vertical modifier in the vertical modifier solution is 0.1 to 10 wt %.
[0016] Preferably, the concentration of the vertical modifier in the vertical modifier solution is 0.15 to 5 wt %.
[0017] Preferably, the concentration of the vertical modifier in the vertical modifier solution is 0.25-1 wt %.
[0018] Specifically, optionally, the vertical modifier is DMOAP.
[0019] Specifically, the mass fraction of DMOAP in the vertical modifier solution is 0.25-0.5%.
[0020] In one embodiment of the present invention, the colorless transparent material includes a cellulose transparent film, a polyurethane transparent film, a glass slide or a hydrogel transparent film.
[0021] In one embodiment of the present invention, the size of the colorless transparent material is 5-100×5-100 mm, and the height is 1-10 mm.
[0022] In one embodiment of the present invention, the material of the slide glass includes glass or quartz.
[0023] In one embodiment of the present invention, the support grid is a thin sheet mesh structure; the aperture of a single mesh in the mesh structure is 25 to 300 μm, and the hole depth is 0.05 to 20 μm.
[0024] Preferably, the aperture of a single mesh in the mesh structure is 100-150 μm, and the pore depth is 1-10 μm.
[0025] In one embodiment of the present invention, the shape of a single grid in the mesh structure is not limited and may be circular, square, trapezoidal or irregular.
[0026] In one embodiment of the present invention, the material of the support grid is an inert material; the inert material includes one or more of copper, aluminum, zinc, tin, and stainless steel.
[0027] In one embodiment of the present invention, the composite liquid crystal system consists of liquid crystal and an additive.
[0028] In one embodiment of the present invention, the liquid crystal includes nematic liquid crystal, cholesteric liquid crystal or chiral nematic liquid crystal.
[0029] In one embodiment of the present invention, the nematic phase liquid crystal includes one or more of 5CB (4-cyano-4'-pentylbiphenyl), 7CB (4-cyano-4'-heptylbiphenyl), 8CB (4-cyano-4'-(n-octyloxy)biphenyl), and E7 (a commercial liquid crystal material mixed with multiple nematic phase liquid crystals).
[0030] In one embodiment of the present invention, the cholesteric liquid crystal includes one or more of cholesterol nonanoate, cholesterol chloride, cholesterol oleyl carbonate, cholesterol acetate, cholesterol propionate, cholesterol butyrate, cholesterol oleate, cholesteryl linoleate, cholesterol benzoate, cholesterol cinnamate, cholesterol ethyl carbonate, cholesteryl isostearyl carbonate, cholesteryl butyrate, and cholesteryl carbonate.
[0031] In one embodiment of the present invention, the chiral nematic liquid crystal is composed of a chiral additive and E7; the chiral additive includes one or more of S811, S1011, R811, R6N, R5011, R1011, and CB15.
[0032] Preferably, the liquid crystal is a nematic phase liquid crystal, including 5CB, 7CB, 8CB or E7.
[0033] In one embodiment of the present invention, the dopant includes one or more of P-type nickel oxide nanomaterials, indium oxide-nickel oxide heterojunctions, zinc oxide-nickel oxide heterojunctions, and zinc stannate-nickel oxide nanoflowers.
[0034] Preferably, the dopant is P-type nickel oxide nanomaterial.
[0035] In one embodiment of the present invention, the P-type nickel oxide nanomaterial includes P-type nickel oxide nanoparticles, P-type nickel oxide nanowires or P-type nickel oxide nanosheets.
[0036] Furthermore, the particle size of the P-type nickel oxide nanoparticles is 5 to 15 nm.
[0037] Furthermore, the length of the P-type nickel oxide nanowire is 5 to 500 μm, and the diameter is 50 to 200 nm.
[0038] Furthermore, the thickness of the P-type nickel oxide nanosheet is 5-50 nm and the area is 50-200×50-200 nm. 2 .
[0039] In one embodiment of the present invention, the preparation method of the dopant includes one or more of a hydrothermal method, a solvothermal method, a sol-gel method, and a chemical precipitation method.
[0040] In one embodiment of the present invention, the mass fraction of the dopant in the composite liquid crystal system is 0.01-1%.
[0041] Preferably, the mass fraction of the dopant in the composite liquid crystal system is 0.025-0.05%.
[0042] The second object of the present invention is to provide a method for preparing a highly sensitive micron liquid crystal sensor for detecting propanol gas, the method comprising the following steps:
[0043] (1) stirring and mixing the liquid crystal and the dopant to uniformly prepare a composite liquid crystal system;
[0044] (2) washing or soaking the colorless transparent material with a vertical modifier solution, and then drying the washed colorless transparent material to obtain a substrate;
[0045] (3) Placing a support grid on a substrate, and then filling the composite liquid crystal system into the support grid to obtain a highly sensitive micron liquid crystal sensor.
[0046] Furthermore, in step (1), the stirring speed is 500 to 1000 rpm, and the stirring time is 30 to 60 min.
[0047] Furthermore, the uniform mixing in step (1) means that there are no large particles of nanomaterial agglomerates in the composite liquid crystal system, and the color of the liquid crystal itself is not covered by the dopant.
[0048] Furthermore, in step (2), the drying is performed by placing the product at a temperature of 50 to 100° C. for 10 min to 24 h.
[0049] The high-sensitivity micron liquid crystal sensor provided by the present invention is applied in the field of propanol detection.
[0050] Application of the high-sensitivity micron liquid crystal sensor provided by the present invention in the preparation of propanol detection equipment or devices.
[0051] The present invention also provides a method for detecting propanol using the above-mentioned high-sensitivity micron liquid crystal sensor. The method comprises placing the high-sensitivity micron liquid crystal sensor in an environment, and then placing the high-sensitivity micron liquid crystal sensor under a polarizing microscope for observation.
[0052] In one embodiment of the present invention, if the light spot area is observed to be 0, there is no propanol in the environment, and if the light spot appears, there is propanol in the environment.
[0053] In one embodiment of the present invention, the standing time is no more than 15 days and no less than 1 minute.
[0054] Specifically, the dopant used in the present invention is P-type nickel oxide nanomaterial, which is doped into the nematic phase liquid crystal to form a composite liquid crystal system. At the same time, a vertical modifier is used to modify the glass substrate to prepare a substrate, and a liquid crystal support grid is placed on it. The liquid crystal composite system is evenly filled into the grid in a certain way to form a three-layer stable sensing system of micron liquid crystal-support grid-modified substrate, thereby preparing a liquid crystal sensor for detecting propanol gas.
[0055] As a semiconductor metal oxide, P-type nickel oxide has certain gas-sensitive properties. This type of material has a large specific surface area, uniform size, and a loose and porous microstructure. Based on the ion adsorption model and the oxygen vacancy model, a large number of adsorbed oxygen ions and electron hole accumulation layers are formed on the surface. The reducing gas can exchange electrons with the oxidizing oxygen anions in the hole accumulation layer, fill the holes, change the conductivity of the material, and show responsiveness, so it can respond quickly and sensitively to trace amounts of reducing gas propanol in the environment. The material is doped in the liquid crystal system. Since the nanomaterial size is extremely small, it can be filled between liquid crystal molecules to form a liquid crystal composite system. The present invention uses a micron grid support structure to provide space for the liquid crystal composite material, so that most of the liquid crystal molecules can form an anchoring effect with the modifier molecules of the substrate, and then unify the orientation. At the same time, the micron grid limits the overall flow trend of the liquid crystal. Under the dual effect of the support grid, the liquid crystal molecules have a stable and uniform molecular orientation and arrangement. In the propanol atmosphere, the P-type nickel oxide nanomaterial transmits its own response to the propanol gas to the liquid crystal molecules, changes the initial orientation of the liquid crystal molecules, and realizes the optical response change from dark state to bright state under specific optical conditions. In summary, the sensor achieves rapid and sensitive detection of trace amounts of propanol gas with its micron structure. The space required for detection is very small, the preparation and operation are simple, and the economic cost is low.
[0056] The beneficial effects of the present invention are:
[0057] The present invention constructs a new liquid crystal composite sensing system, using P-type semiconductor nickel oxide nanomaterials as the response material for propanol gas, and using the orientation characteristics of liquid crystals to express the sensing signal in an optical form, thereby preparing a liquid crystal sensor that can be portable and efficient in detecting propanol gas, with a simple preparation method and high economic benefits. Based on the excellent gas adsorption of P-type nickel oxide nanomaterials, the sensor can respond quickly and sensitively to trace propanol gas (10ppm), and the results are easy to observe, which is suitable for most propanol gas detection scenarios.
[0058] The propanol gas liquid crystal sensor produced by the present invention has certain stability, reversibility and anti-interference. Based on the control of the liquid crystal orientation by the substrate, the liquid crystal system is stable, can be placed for 15 days and still respond to propanol, and is not easily disturbed by the external environment, and does not respond to other alcohols and common organic reagents. After the response, it can be restored, can be repeatedly detected, and has a long effective use period. The liquid crystal sensor provided by the present invention has great application prospects in the fields of chemical industry, medical treatment, environmental monitoring, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is the schematic diagram of the liquid crystal sensor's response to propanol gas.
[0060] Figure 2These are optical images before and after the response of the P-type nickel oxide nanoparticle-doped liquid crystal sensor to VOC vapors of different concentrations in Example 1. DETAILED DESCRIPTION
[0061] The present invention is further described below through specific examples, but the embodiments of the present invention are not limited thereto.
[0062] Source of raw materials
[0063] Liquid crystals such as 5CB were purchased from Beijing Bayi Space-Time Liquid Crystal Technology Co., Ltd.; Decon90, nickel nitrate hexahydrate, indium chloride tetrahydrate, and anhydrous ethanol were purchased from Sinopharm Chemical Reagent Co., Ltd.; DMOAP was purchased from Sinopharm Chemical Reagent Co., Ltd.; microscope slides were conventional commercial products with a size of 25×75 mm, 1 mm-1.2 mm; copper sheets were purchased from Micro toNano (UK).
[0064] Preparation method of P-type nickel oxide nanoparticles: dissolve nickel nitrate hexahydrate and ammonium bicarbonate in 150 mL of deionized water at a molar ratio of 1:2, add 100 mL of anhydrous ethanol, and stir at 60°C to obtain a green solution. Centrifuge the obtained solution to obtain a precipitate. Dry the precipitate in an oven at 80°C for 12 hours to obtain a precursor. Calcinate the obtained precursor at 250°C for 1 hour to finally obtain P-type nickel oxide nanoparticles with a particle size of 6.5 to 10 nm.
[0065] Preparation method of P-type nickel oxide nanowires: dissolve 0.475g nickel nitrate hexahydrate into a 50mL beaker containing 15mL deionized water, stir evenly, add 0.134g sodium oxalate, 0.1g polyethylene glycol and 25mL ethylene glycol, stir again to finally form a transparent solution, transfer to a high-pressure reactor, calcine at 180°C for 15h, obtain a blue-green product, centrifuge several times, wash with ethanol and deionized water to remove impurity ions, and finally dry in vacuum at 60°C to obtain a precursor. The obtained precursor is calcined at 400°C for 2h to finally obtain P-type nickel oxide nanowires with a length of 10-12μm and a diameter of 80-100nm.
[0066] Preparation method of P-type nickel oxide nanosheets: Dissolve 0.475g of nickel nitrate hexahydrate in a beaker containing 25mL of deionized water and 15mL of ethylene glycol, and stir evenly to form a green transparent solution. Add 25% ammonia water drop by drop until the pH value of the overall solution reaches 9.5, transfer to a reactor after stirring for 5 minutes, and calcine at 140°C for 12h. The green product is obtained, centrifuged several times, and washed with ethanol and deionized water to remove impurity ions, and finally vacuum dried at 60°C to obtain a precursor. The precursor is calcined at 450°C for 2h, and finally a square P-type nickel oxide nanosheet with a thickness of 30nm and a side length of 150nm is obtained.
[0067] Example 1
[0068] 1. Preparation of Liquid Crystal Doped P-type Semiconductor Nickel Oxide Nanomaterial Composite System
[0069] A certain amount of 5CB (4-cyano-4'-pentylbiphenyl) liquid crystal is mixed with P-type nickel oxide nanoparticles, P-type nickel oxide nanowires, and P-type nickel oxide nanosheets prepared by a hydrothermal method in a beaker, and the mass fraction of the dopant (nanoparticles, nanowires, nanosheets) is controlled to be 0.05%. After adding a magnetic rotor, the mixture is placed on a magnetic stirrer at room temperature and stirred at 500 rpm for 1 h or 1000 rpm for 30 min (the speed and time can be adjusted as appropriate) until the P-type nickel oxide nanomaterial is evenly dispersed in the liquid crystal system, thereby obtaining a liquid crystal composite material. The obtained material is sealed for later use.
[0070] 2. Preparation of liquid crystal glass substrate using vertical modifier DMOAP
[0071] (1) Slide cleaning
[0072] Soak the microscope slide in Decon-90 detergent for 1 hour or immerse the microscope slide in a beaker of Decon-90 and place it in an ultrasonic cleaner for 20 minutes. Then rinse the residual detergent thoroughly with anhydrous ethanol and deionized water in turn, blow dry the liquid on the surface of the slide with nitrogen, place it in a 60°C oven to dry for about 15 minutes, take it out and protect it from dust for later use.
[0073] (2) Preparation of vertical modifier solution
[0074] A certain amount of DMOAP liquid was taken with a plastic dropper and dropped into a beaker containing deionized water to control the mass fraction of DMOAP to 0.25%. After adding a magnetic rotor, the mixture was placed on a magnetic stirrer at room temperature and stirred at 500 rpm for 10 min to form a transparent DMOAP aqueous solution, which was then sealed for later use.
[0075] (3) Preparation of modified glass substrate
[0076] Use a plastic dropper to absorb the above DMOAP aqueous solution and evenly rinse the cleaned glass slide for 1 minute. Then rinse with a large amount of deionized water, blow dry with nitrogen, and place in a 100°C oven to dry for 15 minutes to obtain a modified glass substrate, which is dust-proof and ready for use.
[0077] 3. Preparation and response performance test of high-sensitivity micron liquid crystal sensor for detecting propanol gas
[0078] (1) Preparation of liquid crystal sensor
[0079] Use a capillary to absorb 0.5 μL of the prepared liquid crystal composite material and drop it on the modified glass substrate. Use special curved-tip tweezers for copper sheets to cover a 3.05 mm × 3.05 mm copper sheet with holes (aperture of 150 μm and hole depth of 5 μm) on the liquid crystal droplets, use absorbent paper to absorb the overflowed liquid crystal from the outer edge of the grid, and use the fluidity of the liquid crystal to fill the liquid crystal material into the grid to obtain a liquid crystal sensor. After that, a polarized light microscope can be used to check the filling state of the liquid crystal in the copper mesh. When the optical image of the liquid crystal in the grid presents a uniform dark field and there is no protruding or concave bright edge, it can be ensured that the liquid crystal material just fills the grid without gaps or overflow.
[0080] (2) Response performance test
[0081] Take a certain amount of propanol liquid and add it to deionized water to prepare a 0.33-33.34 mg / mL propanol aqueous solution. Use a 2.5 μL pipette to transfer 1.0 μL of the above solution and drop it on the filter paper in a 10 mL sterile syringe. The syringe needle cap is a special resin sealed needle cap. The syringe pusher is mechanically maintained at the 10 mL scale. Use an electric blower to heat until the liquid on the filter paper is completely evaporated. Turn off the electric blower and wait for the syringe temperature to drop to room temperature 20-25°C, that is, 10-1000 ppm propanol vapor at room temperature has been formed in the syringe. Slowly push the propanol gas through the syringe to the liquid crystal sensor prepared above, and keep the gas in contact with the liquid crystal sensor for 1-5 minutes. Place the sensor under a polarizing microscope to respond to the propanol gas, and observe the optical image of the liquid crystal material. The results are shown in Tables 1 and Figure 2 shown.
[0082] The results show that when the sensor does not respond to propanol gas, the sensor presents a uniform dark field of view. When the sensor is exposed to propanol gas of various concentrations, the image of the liquid crystal sensor undergoes obvious optical changes, from a dark state to a bright field of view, generating a large number of light spots, indicating that the liquid crystal sensor has a good response effect to propanol vapor and can achieve a sensitivity of detecting 10ppm trace propanol gas. The sensing performance of the sensors prepared by the three types of dopants is almost the same. The optical brightness of nickel oxide nanowires and nanosheets is slightly worse in the presence of trace propanol gas, but the light spot area is larger. Comprehensively considering various response performances, the liquid crystal sensor doped with nickel oxide nanoparticles has the best response effect.
[0083] Table 1 Response performance of liquid crystal sensors prepared with different dopants to different concentrations of propanol gas
[0084]
[0085] (Note: The brightness level is based on the response of the liquid crystal sensor to 1000ppm propanol gas in this embodiment, and is divided into four categories: bright, relatively bright, relatively dark, and dark; the spot area is expressed as the percentage of the bright part to the total area of the 4×4 grid, and is divided into 100%, 75%, 50%, 25%, and 0%. The data classification of the tables of the subsequent embodiments and comparative examples is the same as this.)
[0086] Example 2
[0087] The liquid crystal sensor prepared in Example 1 is placed in a closed gas generation diffusion system for response performance test, and the specific steps are as follows: the liquid crystal sensor is placed in a 500mL transparent metal airtight box, the air outlet of the airtight box is aligned and kept at a distance of 3 to 5cm. Take 0.0167 to 1.67mg of propanol liquid, configure it into 50mL propanol aqueous solution, store it in a 250mL supported conical flask, place the conical flask on a non-magnetic stirring heating table and heat it at 98°C, and produce propanol vapor through a rubber tube connected between the airtight box and the conical flask to the airtight box, and wait for the vapor to exist stably, that is, 10 to 1000ppm propanol vapor is formed in the airtight box. The liquid crystal sensor responds in a propanol atmosphere. Then the airtight box equipped with the sensor is placed under a polarizing microscope for response, and the optical image of the liquid crystal material is observed. The results are shown in Table 2.
[0088] The results show that when the sensor is in a propanol atmosphere in a confined space, the optical changes in the image of the liquid crystal sensor are basically the same as those in Example 1, and the spot area is larger. This shows that the propanol gas is more evenly dispersed in the confined environment and has more complete contact with the liquid crystal sensor, making the sensing effect more uniform.
[0089] Table 2 Response performance of liquid crystal sensor to different concentrations of propanol gas in a closed environment
[0090]
[0091] Example 3
[0092] The P-type nickel oxide nanoparticle-doped liquid crystal sensor prepared in Example 1 was placed in an open environment at normal temperature and pressure (25°C, 101.325 kPa) and normal humidity (50%) for 0.5 to 15 days. During the placement process, a response test was performed using 10 to 1000 ppm propanol vapor, and the same liquid crystal sensor was subjected to a response test again after a certain interval. The test process was consistent with that in Example 1. The results are shown in Table 3.
[0093] The results show that the liquid crystal sensor has the ability to restore its orientation and a certain response performance after being placed for different periods of time. This shows that after being placed in a normal environment, the liquid crystal sensor has not been completely disturbed by the previously tested propanol gas and the external environment, and has good stability and reusability.
[0094] Table 3 Response performance of liquid crystal sensor to propanol gas after being placed for different days
[0095]
[0096]
[0097] (Note: The degree of orientation recovery at a certain placement time in the table is the degree of orientation recovery of the same liquid crystal sensor after the last response performance test.)
[0098] Example 4
[0099] The mass fraction of the vertical modifier solution in Example 1 was adjusted to 0-0.5%, the speed of the magnetic stirrer was adjusted to 0-1000 rpm, the stirring time and the speed were appropriately adjusted according to the dissolution state of DMOAP in the aqueous solution until it was completely dissolved, and the other processes were consistent with the steps of preparing the glass substrate in Example 1. The results are shown in Table 4.
[0100] The results show that the liquid crystal composite material on the glass substrate without DMOAP modification has a disordered orientation, while the modified glass substrate surface can make the liquid crystal material present a uniform black image in the grid, and the higher the concentration of DMOAP aqueous solution, the more complete the vertical orientation. When the mass fraction is above 0.25%, the degree of liquid crystal orientation remains almost unchanged, because at this concentration, the substrate can ensure the vertical orientation of all liquid crystal molecules, the sensor grid is completely dark, and no longer changes with the increase of mass fraction. Considering economic benefits, 0.25% DMOAP aqueous solution can be used as the optimal mass fraction of glass substrate modifier.
[0101] Table 4 Effect of different mass fractions of vertical modifiers on the degree of liquid crystal orientation
[0102]
[0103] (Note: The degree of orientation of liquid crystal molecules on the glass substrate is based on the modifier mass fraction of 0.25%, which is divided into disordered, partially vertical and completely vertical. The classification of related data in the table is the same.)
[0104] Example 5
[0105] The mass fraction of the P-type nickel oxide nanoparticles in Example 1 was adjusted to 0.01-1%. The rotation speed and stirring time were appropriately adjusted during stirring until the nanoparticles at each mass fraction were uniformly dispersed in the 5CB liquid crystal. 10-1000 ppm propanol vapor was used for response testing. The other processes were consistent with Example 1. The results are shown in Table 5.
[0106] The results show that when the mass fraction of P-type nickel oxide nanoparticles is 0.025%, 0.05%, 0.1%, and 0.5%, the prepared liquid crystal sensor can respond to 10-1000ppm propanol vapor, indicating that the liquid crystal molecules are affected by the absorption of gas by the dopant nanoparticles, and the molecular orientation changes. Among them, the response effect is better when the mass fraction of P-type nickel oxide nanoparticles is between 0.025 and 0.05%. At a high mass fraction such as 1%, the nanoparticles will agglomerate to form large particles, affecting the response effect of the liquid crystal sensor, which is not conducive to the observation and response of the sensor.
[0107] Table 5 Response performance of liquid crystal sensors prepared with different mass fractions of dopants to propanol gas
[0108]
[0109] Comparative Example 1
[0110] Only the liquid crystal material in Example 1 was adjusted to nematic phase liquid crystals 7CB (4-cyano-4'-heptylbiphenyl), 8CB (4-n-octyl-4'-cyanobiphenyl) and E7, and the dopant was still P-type nickel oxide nanoparticles. The response test to 10-1000 ppm propanol vapor was carried out. The other processes were consistent with Example 1. The results are shown in Table 6.
[0111] The results show that by changing different nematic phase liquid crystals, the optical changes produced by the liquid crystal sensor in response to propanol gas are basically the same, and the area and brightness of the bright spot are slightly reduced. This may be because the molecular weight of the liquid crystal molecules increases, making it more difficult for the nickel oxide dopant to affect the orientation of the liquid crystal molecules after absorbing the gas, so the response effect is slightly worse than the liquid crystal sensor prepared in Example 1.
[0112] Table 6 Response performance of different nematic phase liquid crystal sensors to 10-1000 ppm propanol gas
[0113]
[0114] Comparative Example 2
[0115] Only the liquid crystal material in Example 1 is adjusted to be a mixed cholesteric liquid crystal and liquid crystal E7 with a chiral agent S811 added. Among them, the mixed cholesteric liquid crystal is COC (cholesterol oleyl carbonate), CN (cholesterol nonanoate), and CC (cholesterol chloride) mixed in a beaker at a mass ratio of 5:5:3, and a magnetic rotor is added and placed on a magnetic stirrer to stir evenly to obtain a cholesteric liquid crystal CLC. The CLC is heated to above the clearing point, P-type nickel oxide nanoparticles are added, the doping mass fraction is controlled to be 0.05%, and the temperature is kept above the clearing point and mixed and stirred at 500rpm for 1h until the nickel oxide particles are evenly dispersed; E7 is mixed with the chiral additive S811 at 7:3 to form a chiral nematic liquid crystal, P-type nickel oxide nanoparticles are added thereto, the doping mass fraction is controlled to be 0.05%, and the nickel oxide particles are evenly dispersed at 500rpm. This comparative example uses 1000ppm propanol vapor for response testing, and the other processes are consistent with Example 1. The results are shown in Table 7.
[0116] The results show that the initial orientation of the sensor made of cholesteric liquid crystal and chiral nematic liquid crystal composite material is chaotic, there are light spots (bright state) before and after the response performance test, and the optical changes in response to propanol gas are not easy to observe. Since the molecules of these two liquid crystal materials are in a spiral arrangement structure and the viscosity of the liquid crystal material is relatively high, it is difficult to form a uniform molecular arrangement in the supporting grid, so the overall optical image is relatively chaotic, which will cause difficulties in use and observation.
[0117] Table 7 Response performance of chiral nematic liquid crystal and cholesteric liquid crystal sensors to 1000ppm propanol gas
[0118]
[0119] Comparative Example 3
[0120] Only the dopant of the liquid crystal system is adjusted to nickel oxide nanoparticles and indium oxide-nickel oxide heterojunctions, silver-modified nickel oxide nanoparticles, and zinc stannate-nickel oxide nanoflowers prepared by the sol-gel method.
[0121] The sol-gel method for preparing nickel oxide nanoparticles is as follows: nickel acetate tetrahydrate and zinc acetate are dissolved in ethylene glycol monomethyl ether solution at a molar ratio of 25:1, and magnetically stirred at 60°C for 1 hour. A small amount of ethanolamine solution is added dropwise, one drop per second, until a uniformly distributed dark green solution is formed. The mixed solution is heated in a boiling furnace at 60°C for 2 hours and then allowed to stand at room temperature for 24 hours to obtain nickel oxide nanoparticles.
[0122] The preparation method of the indium oxide-nickel oxide heterojunction is as follows: 4.73g nickel sulfate hexahydrate and 1.06g indium chloride tetrahydrate are dissolved in 180mL deionized water, 1g potassium persulfate and 3mL ammonia solution are added under stirring, and stirring is continued for 20min. The above solution is centrifuged to obtain an intermediate product, which is washed with deionized water and dried in air at 60°C, and then annealed at 600°C for 4h to obtain an indium oxide-nickel oxide heterojunction material.
[0123] The preparation method of silver-modified nickel oxide nanoparticles is as follows: nickel nitrate hexahydrate and ammonium bicarbonate (molar ratio 1:2) and a small amount of silver nitrate are dissolved in 150 mL of deionized water, 100 mL of anhydrous ethanol is added, and a green solution is obtained by stirring at 60°C. The obtained solution is centrifuged to obtain a precipitate. The precipitate is placed in an oven at 80°C and dried for 12 hours to obtain a precursor. The obtained precursor is calcined at 250°C for 1 hour to finally obtain P-type nickel oxide nanoparticles with a particle size of 6.5 to 10 nm.
[0124] The preparation method of zinc stannate-nickel oxide nanoflowers is as follows: 50 mg of zinc stannate nanoflowers are ultrasonically dispersed in 10 mL of anhydrous ethanol for 20 minutes, and an appropriate amount of nickel nitrate hexahydrate is added under magnetic stirring at room temperature until the ethanol is basically evaporated. The product is dried at 70°C overnight and calcined at 500°C for 2 hours to obtain zinc stannate-nickel oxide nanoflowers.
[0125] The mass percentage of the above dopant was controlled to be 0.05%, and 10-1000 ppm propanol vapor was used for response testing. The other processes were consistent with Example 1. The results are shown in Table 8.
[0126] The results show that the response performance of nickel oxide nanoparticles prepared by the sol-gel method to 1000ppm propanol gas is closest to the results in Example 1, but under low concentration conditions, the response effect is reduced and cannot meet the sensitivity requirements. Other modified nickel oxide doped liquid crystal sensors cannot produce obvious optical responses to propanol gas from high concentration to low concentration, and cannot meet the basic requirements of the present invention.
[0127] Table 8 Response performance of liquid crystal sensors with other types of dopants to 10-1000 ppm propanol gas
[0128]
[0129] Comparative Example 4
[0130] The preparation method of the glass substrate in this comparative example is as follows:
[0131] Take a certain amount of copper perchlorate and dissolve it in anhydrous ethanol to prepare a copper perchlorate anhydrous ethanol solution with a concentration of 50-300mmol / L. Spin 50μL of copper perchlorate solution on a clean glass slide by a spin coater at 4000rpm for 2-5min or soak for 1h, place it in a 100℃ oven to dry for 1d and then keep it dust-proof for use. Copper perchlorate molecules can form a monolayer on the surface of a microscope slide, and anchor the liquid crystal molecules through the coordination of metal ions and cyanide groups to form a vertical orientation. Use 10-1000ppm propanol vapor for response testing, and the other processes are consistent with Example 1. The results are shown in Table 9.
[0132] The results show that the glass substrate modified with 100-300mmol / L copper perchlorate has the best anchoring effect on the liquid crystal composite material. However, when responding to propanol gas, the liquid crystal sensor in the 100mmol / L copper perchlorate group has the best optical response effect. When the concentration of the modifier is too high, the substrate has a greater force on the liquid crystal composite material, and it is more difficult for the gas molecules to change the orientation of the liquid crystal molecules; if the concentration of the modifier is too low, it is impossible to ensure that the orientation is uniform before the sensor responds. Compared with Example 1, the response effect of the liquid crystal sensor to propanol gas in this example is slightly worse, the optical change of the sensor is not obvious enough, the spot area is small, and the brightness is not enough.
[0133] Table 9 Response performance of liquid crystal sensor prepared by copper perchlorate vertical modifier to 10-1000 ppm propanol gas
[0134]
[0135]
[0136] Comparative Example 5
[0137] This comparative example compares the specificity of the liquid crystal sensor. The sensor prepared in Example 1 is still used, and the VOC gas is adjusted to acetic acid (118°C), butanol (100°C), acetone (60°C), benzene (80°C), toluene (110°C), and styrene (145°C) gas (the temperature in brackets is the lowest temperature for generating the corresponding VOC vapor). The other processes are consistent with Example 1. The specific steps are as follows:
[0138] Prepare 10.72mg / mL acetic acid aqueous solution, 13.24mg / mL butanol-water mixture, 10.37mg / mL acetone aqueous solution, 13.95mg / mL benzene-water mixture, 16.45mg / mL toluene-water mixture, 18.60mg / mL styrene-water mixture, use 2.5μL pipette to take 2.5μL of the above substances, drop them on the filter paper in the same 10mL sterile syringe as in Example 1, and heat the syringe pusher at the 10mL scale by mechanical action to form 1000ppm of each VOC vapor. Slowly push the gas to the above-made sensor through the syringe, keep the gas in contact with the sensor for 1 to 5min, and the final results are shown in Table 10.
[0139] The results show that compared with Example 1, the liquid crystal sensor doped with nickel oxide nanoparticles has no obvious response to other VOCs gases, which proves its resistance to gas cross-interference and specificity in detecting propanol gas.
[0140] Table 10 Response performance of liquid crystal sensor to other 1000ppm VOCs gases
[0141]
[0142] In summary, in the preparation method provided by the present invention, the sensing effect is best when the liquid crystal material is nematic phase liquid crystal 5CB, the mass fraction of the glass substrate modifier DMOAP aqueous solution is greater than 0.25%, the liquid crystal can present a uniform vertical orientation effect, and the P-type semiconductor oxide nanomaterial should be nickel oxide nanoparticles, nanowires or nanosheets, and the mass fraction doped in the liquid crystal 5CB is 0.025-0.05%, which can make the liquid crystal sensor respond quickly and sensitively to propanol gas. The liquid crystal sensor in the present invention has obvious effects in detecting propanol gas of various concentrations, and the detection lower limit threshold is 10ppm.
[0143] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A highly sensitive micron liquid crystal sensor for detecting propanol gas, characterized in that: The sensor is composed of a substrate, a support grid and a composite liquid crystal system, wherein the support grid is placed on the substrate and the composite liquid crystal system is filled in the support grid; The substrate is a colorless transparent material that has been rinsed or soaked in a vertical modifier solution; the vertical modifier is an organic silicon modifier including one or more of dimethyl octadecyl [3-(trimethoxysilyl) propyl] ammonium chloride, dimethyl dodecyl [3-(trimethoxysilyl) propyl] ammonium chloride, dimethyl hexadecyl [3-(trimethoxysilyl) propyl] ammonium chloride, and γ-aminopropyl triethoxysilane, or an inorganic salt modifier including one or more of copper perchlorate, iron perchlorate, aluminum perchlorate, and nickel perchlorate; the concentration of the vertical modifier in the vertical modifier solution is 0.1 to 10 wt%; The support grid is a thin sheet mesh structure; the single mesh aperture in the mesh structure is 25 to 300 μm, and the hole depth is 0.05 to 20 μm; The composite liquid crystal system consists of liquid crystal and dopants, the liquid crystal is a nematic phase liquid crystal, the dopants include one or more of P-type nickel oxide nanomaterials, indium oxide-nickel oxide heterojunctions, zinc oxide-nickel oxide heterojunctions, and zinc stannate-nickel oxide nanoflowers, and the mass fraction of the dopants in the composite liquid crystal system is 0.01-1%.
2. The high-sensitivity micron liquid crystal sensor according to claim 1, characterized in that: The concentration of the vertical modifier in the vertical modifier solution is 0.15-5wt%; the vertical modifier is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
3. The high-sensitivity micron liquid crystal sensor according to claim 1, characterized in that: The colorless transparent material includes a cellulose transparent film, a polyurethane transparent film, a glass slide or a hydrogel transparent film.
4. The high-sensitivity micron liquid crystal sensor according to claim 1, characterized in that: The material of the supporting grid is an inert material; the inert material includes one or more of copper, aluminum, zinc, tin, and stainless steel.
5. The high-sensitivity micron liquid crystal sensor according to claim 1, characterized in that: The liquid crystal includes 5CB, 7CB, 8CB or E7.
6. The high-sensitivity micron liquid crystal sensor according to claim 1, characterized in that: The dopant is a P-type nickel oxide nanomaterial.
7. The high-sensitivity micron liquid crystal sensor according to claim 1, characterized in that: The mass fraction of the dopant in the composite liquid crystal system is 0.025-0.05%.
8. A method for preparing the highly sensitive micron liquid crystal sensor according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) The liquid crystal and the dopant are stirred and mixed uniformly to obtain a composite liquid crystal system; uniform mixing means that there are no large particles of nanomaterial agglomerates in the composite liquid crystal system, and the color of the liquid crystal itself is not covered by the dopant; (2) washing or soaking the colorless transparent material with a vertical modifier solution, and then drying the washed colorless transparent material to obtain a substrate; (3) Placing a support grid on a substrate, and then filling the composite liquid crystal system into the support grid to obtain a highly sensitive micron liquid crystal sensor.
9. Use of the highly sensitive micron liquid crystal sensor according to any one of claims 1 to 7 in the field of propanol detection or in the preparation of propanol detection equipment.
10. A method for detecting propanol using the highly sensitive micron liquid crystal sensor according to any one of claims 1 to 7, characterized in that: The method comprises placing the high-sensitivity micron liquid crystal sensor in an environment, and then placing the high-sensitivity micron liquid crystal sensor under a polarizing microscope for observation; if a light spot area of 0 is observed, there is no propanol in the environment, and if a light spot appears, there is propanol in the environment.
Citation Information
Patent Citations
Microporous hollow nickel oxide gas-sensitive sensor used for formaldehyde selective adsorption and preparation and application
CN106248744A
Gas sensor based on selective wave bands and detection method thereof
CN106841067A
Nano zinc oxide rod doped polymer dispersed liquid crystal gas sensor
CN109507252A
Gas sensor array and method for identifying three alcohol types and concentrations thereof
CN113030194A
Gas sensitive material, gas sensitive sensor as well as preparation method and application of gas sensitive material
CN114839232A